Advances in material science and engineering selected articles from ICMMPE 2020 - Awang, Mokhtar; Emamian, Seyed Sattar (Springer, 2021)
This book presents selected papers from the 6th International Conference on Mechanical, Manufacturing and Plant Engineering (ICMMPE 2020), held virtually via Google Meet. It highlights the latest advances in the emerging area, brings together researchers and professionals in the field and provides a valuable platform for exchanging ideas and fostering collaboration. Joining technologies could be changed to manufacturing technologies. Addressing real-world problems concerning joining technologies that are at the heart of various manufacturing sectors, the respective papers present the outcomes of the latest experimental and numerical work on problems in soldering, arc welding and solid-state joining technologies.